Templates for writing PyMOL scripts - Mooers, Blaine H. M. (Protein Sci, 2020)
PyMOL commands are used to exert exquisite control over the appearance of a molecular model. This control has made PyMOL popular for making images of protein structures for publications and presentations. However, many users have poor recall of the commands due to infrequent use of PyMOL. This poor recall hinders the writing of new code in scripts. One solution is to build the new script by using code fragments as templates for modular parts of the task at hand. The code fragments can be accessed from a library while writing the code from inside a text editor (e.g., Visual Studio Code, Vim, and Emacs). We developed a library of PyMOL code templates or snippets called pymolsnips to ease the writing of PyMOL code in scripts. We made pymolsnips available on GitHub in formats for 18 popular text editors. Most of the supported text editors are available for Mac, Windows, and Linux operating systems. The GitHub site includes animations that complement the instructions for installing the library for each text editor. We expect that the library will help many PyMOL users to be more productive when writing PyMOL script files.